2019
DOI: 10.1017/wsc.2019.69
|View full text |Cite
|
Sign up to set email alerts
|

Interference of Annual Sowthistle (Sonchus oleraceus) in Wheat

Abstract: Annual sowthistle (Sonchus oleraceus L.) is a broadleaf weed that is increasing in prevalence in the northern cropping regions of Australia. Being a member of Asteraceae family, this weed possesses many biological attributes needed to thrive in varying environments and weed management pressure. Interference of this weed was examined in a wheat (Triticum aestivum L.) crop through field studies in 2016 and 2017. Different densities of S. oleraceus were evaluated for their potential to cause yield loss in wheat: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…In our study, a density of more than 20 plants m −2 could be a critical density since it is associated with significant yield losses ranging between 5% to 20% as reported previously [ 25 , 26 ]. Several studies related to the competitive ability of broad-leaved weeds in wheat pointed out the negative correlation between crop yield and weed density [ 27 , 28 , 29 ]). For a high density of 80 plants m −2 , Galium aparine , a troublesome weed in winter wheat, reduced the grain yield by 31.5% [ 28 ], reaching 57% in other studies in England [ 27 ], Our results indicated that G. coronaria caused 72% of yield losses for the same density (based on sigmoidal curve equation); thus, G. coronaria is likely more competitive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, a density of more than 20 plants m −2 could be a critical density since it is associated with significant yield losses ranging between 5% to 20% as reported previously [ 25 , 26 ]. Several studies related to the competitive ability of broad-leaved weeds in wheat pointed out the negative correlation between crop yield and weed density [ 27 , 28 , 29 ]). For a high density of 80 plants m −2 , Galium aparine , a troublesome weed in winter wheat, reduced the grain yield by 31.5% [ 28 ], reaching 57% in other studies in England [ 27 ], Our results indicated that G. coronaria caused 72% of yield losses for the same density (based on sigmoidal curve equation); thus, G. coronaria is likely more competitive.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, G. coronaria competes vigorously with winter wheat, like previous known troublesome weeds. In fact, weeds from the Asteraceae family are very competitive due to their vigorous growth and potential to exploit available resources [ 29 , 32 ]. This competitive ability of G. coronaria and it is associated wheat yield penalty emphasize the need for correct weed management decisions.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study conducted in the state of Queensland, 43 to 52 plants/m 2 caused a yield reduction of 50% in wheat [2]. In the same study, this weed produced up to 193,000 seeds/m 2 .…”
Section: Introductionmentioning
confidence: 85%
“…Annual sowthistle (Sonchus oleraceus L.) is one of the most troublesome weeds in terms of revenue loss in Australia (AU$4.9 million) (Llewellyn et al 2016). It is estimated that the presence of 43 to 52 S. oleraceus plants m −2 could reduce wheat (Triticum aestivum L.) yield by 50% (Manalil et al 2020). Abundant seed production, no to very low seed dormancy, and tolerance to a broad range of environmental conditions are factors that contribute to S. oleraceus emergence throughout the year (summer and winter) in many cropping systems (Chauhan et al 2006;Manalil et al 2018;Widderick et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Sonchus oleraceus biotypes resistant to glyphosate (5-enolpyruvylshikimate-3phosphate synthase inhibitor) and 2,4-D (synthetic auxin) have also been reported in Australia in the last decade (Heap 2020). Low seed retention (95% wind dispersal), resistance to several herbicides, and the high competitiveness of this weed have reduced the effectiveness of existing weed control practices, making S. oleraceus a challenging issue in Australian agricultural systems (Manalil et al 2020;Mobli et al 2019).…”
Section: Introductionmentioning
confidence: 99%